2020
DOI: 10.1016/j.mehy.2020.109935
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A and TNF-α as potential biomarkers for acute respiratory distress syndrome and mortality in patients with obesity and COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) was declared a pandemic and international health emergency by the World Health Organization. Patients with obesity with COVID-19 are 7 times more likely to need invasive mechanical ventilation than are patients without obesity (OR 7.36; 95% CI: 1.63–33.14, p = 0.021). Acute respiratory distress syndrome (ARDS) is one of the main causes of death related to COVID-19 and is triggered by a cytokine storm that damages the respiratory epithelium. Interleukins that cause the chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 45 publications
(51 reference statements)
2
55
0
2
Order By: Relevance
“…Chronic elevations of pro-inflammatory cytokines, such as TNF-α and IL-6, also directly influence COVID-19 disease course. Because TNF-α plays an important role in promoting ARDS, obese individuals with chronically elevated serum TNF-α are at greater risk of developing this life-threatening complication [ 102 ]. In patients with COVID-19, IL-6 levels are significantly elevated and associated with adverse clinical outcomes.…”
Section: Underlying Mechanisms Linking Obesity To Major Complications As a Results Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Chronic elevations of pro-inflammatory cytokines, such as TNF-α and IL-6, also directly influence COVID-19 disease course. Because TNF-α plays an important role in promoting ARDS, obese individuals with chronically elevated serum TNF-α are at greater risk of developing this life-threatening complication [ 102 ]. In patients with COVID-19, IL-6 levels are significantly elevated and associated with adverse clinical outcomes.…”
Section: Underlying Mechanisms Linking Obesity To Major Complications As a Results Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Since serum concentration of TNF-α is elevated in COVID-19 patients [ 31 ], and also during low-grade chronic inflammation in the obese, inflammation and thrombosis could both be attributed to the increased TNF-α activity. Therefore, serum TNF-α could be considered as potential biomarker in acute respiratory distress syndrome (ARDS) in obese COVID-19 patients [ 32 ], and thus can be targeted to control the severity of the disease.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…In this study, we found that Quercetin is capable of binding with the active site of ACE2 by forming conventional hydrogen bond and Pi-Alkyl interactions with amino acids TRP 69 , LEU 391 , LEU 73 and ALA 99 . Besides, the activation of TNF and NF-кB signaling pathways were identified as the novel changes in the pathogenesis of COVID-19 [ 57 59 ]. Our data from network pharmacology also suggested that five signaling pathways including TNF, HIF-1α, TLR, apoptosis-related, and VEGF signaling may be the therapeutic pathways in Quercetin treatment to COVID-19-induced AKI.…”
Section: Discussionmentioning
confidence: 99%